2022
DOI: 10.5114/kitp.2022.119760
|View full text |Cite
|
Sign up to set email alerts
|

Transatrial-transpulmonary correction of tetralogy of Fallot: experience of a developing country

Abstract: Introduction: Right ventricular dysfunction is a cause of morbidity and mortality after surgical correction of tetralogy of Fallot. The transatrial-transpulmonary approach allows preservation of right ventricular function. Aim: To report the immediate and long-term results of surgical treatment of tetralogy of Fallot using the transatrial-transpulmonary approach. Material and methods: This is a retrospective study including cases of tetralogy of Fallot operated on by the transatrial-transpulmonary approach bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Indeed, more than half of the patients experienced dyspnea, syncope, chest pain, and seizures. 12 , 13 , 17 , 21 , 22 , 23 In HICs, patients are typically operated pre-emptively between 3 and 11 months or as an emergency after the appearance of ToF spells. In contrast, the International Quality Improvement Collaborative for Congenital Heart Disease (IQIC), a study regrouping >2000 patients from 32 centres in 20 LMICs, found that 54% of patients operated on for ToF were over 1 year old.…”
Section: Burden Of Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, more than half of the patients experienced dyspnea, syncope, chest pain, and seizures. 12 , 13 , 17 , 21 , 22 , 23 In HICs, patients are typically operated pre-emptively between 3 and 11 months or as an emergency after the appearance of ToF spells. In contrast, the International Quality Improvement Collaborative for Congenital Heart Disease (IQIC), a study regrouping >2000 patients from 32 centres in 20 LMICs, found that 54% of patients operated on for ToF were over 1 year old.…”
Section: Burden Of Diseasementioning
confidence: 99%
“… 22 45 patients Median age at the time of surgery: 21 years (range: 15-44 years) India 42% of patients with long-standing hypoxia have significant MAPCAs All these patients should have preoperative catheterization Souaga et al. 23 19 patients Mean age at the time of surgery: 7.4 ± 4.52 years Ivory Coast Perioperative mortality = 10.5% mortality Perioperative morbidity = 17.6% of right heart failure, low cardiac output = 11.8%, and transient complete AV block = 5.9% AV, atrioventricular; CHD, congenital heart disease; CHU, Centre Hospitalier Universitaire; LMIC, low- and middle-income country; MAPCA, major aortopulmonary collateral artery; NYHA, New York Heart Association; PRV/LV, right ventricular-left ventricular systolic pressure ratio; RVOT, right ventricular outflow tract; ToF, tetralogy of Fallot. …”
Section: Burden Of Diseasementioning
confidence: 99%